2009
DOI: 10.1902/jop.2009.090013
|View full text |Cite
|
Sign up to set email alerts
|

Bone Strain and Interfacial Sliding Analyses of Platform Switching and Implant Diameter on an Immediately Loaded Implant: Experimental and Three‐Dimensional Finite Element Analyses

Abstract: Bone strain was reduced more by increasing the diameter of the implant than by using platform switching in the immediately loaded implant. However, neither a wide implant nor platform switching reduced micromotion at the BII for enhancing implant stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
1
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 29 publications
4
50
1
4
Order By: Relevance
“…In 2009, Hsu et al analyzed the behavior of reduced platform restorations in the context of a finite elements study in three dimensions. Their results showed a 10% decrease in all the prosthetic loading forces transmitted to the bone-implant interface (15). Similar finite elements studies in two dimensions show great variability in the results obtained.…”
Section: Biomechanical Behaviormentioning
confidence: 65%
See 1 more Smart Citation
“…In 2009, Hsu et al analyzed the behavior of reduced platform restorations in the context of a finite elements study in three dimensions. Their results showed a 10% decrease in all the prosthetic loading forces transmitted to the bone-implant interface (15). Similar finite elements studies in two dimensions show great variability in the results obtained.…”
Section: Biomechanical Behaviormentioning
confidence: 65%
“…Platform expansion in post-extraction situations makes it possible to minimize the gap between the recently extracted tooth bed and the implant, acting as a physical barrier against the penetration of bacteria in the zone of contact between the bone and implant. This increase in diameter favors improved primary stability (15,(28)(29)(30)(31).…”
Section: E404mentioning
confidence: 99%
“…When considering platform-switched implants, previous studies [14,17] have shown an increased stress on the abutment and fixation screw, which may compromise the system biomechanical performance. Controversially, several published studies [1,12,13,15,16,19,[25][26][27] related to the mechanics of platformswitched implants have been restricted to analyzing the stress distribution on peri-implant bone and not on the overall system biomechanical behavior. To date, studies evaluating the mechanical behavior of platform-switched implants considering the stress distribution in implantabutment complex are scarce and restricted to computer simulations [14,17,28,29], which do not consider several clinical variables (influence of fatigue damage accumulation and wet environment) previously reported as important factors to reproduce clinically observed failure modes [30].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, implants were fixed in the alveoli, after tooth extraction, with an immediate temporary restoration, and the definitive implant was placed after 15 days, through the Switching Platform concept. [29] when checking the bone tension and micro-movement at the bone-implant interface for switching platform, simulated finite elements and analysis by extensometry with different diameters of a single implant with immediate loading. They created four models, 5.0 mm diameter implants with prosthetic components 5.0 mm and 4.0 mm in diameter, cemented (late loading) and screwed (immediate loading), and a model with implant of 3.75 Mm diameter, in which vertical and lateral loads of 130 N were applied, which resulted in the following: bone forces were reduced by up to 10% with the use of the switching platform.…”
mentioning
confidence: 99%
“…Hsu et al (2009) [29], when using finite elements in their studies, concluded that there is a 10% reduction in forces exerted on bone when there is the use of the Switching Platform concept in relation to conventional implants and that the increase of implant diameter (Extended platform) led to an expressive reduction of the stress in the surrounding bone to the implant, leading to understand that not only the Switching Platform system, but the increased implant diameter reduces stress in the bone tissue. Still in the same study, they stated that none of the settings used.…”
mentioning
confidence: 99%